COMPARISON PROFIT BUSINESS CATTLE CHICKEN CLOSED HOUSE AND OPEN HOUSE CAGE LAYERS (CASE STUDY IN PAYAKUMBUH ): Inggris - Rudy Kusuma; Fajri, Rahmat; Erwin, Erwin (Journal of Animal Nutrition and Production Science, 2024)
Research This was carried out in the Closed House Taram Farm enclosure located in Jorong Sipatai, Bukik Limbuku, Harau District, Limapuluh Kota Regency and the Open House Sari Farm which is located on Jalan Belubus, Bukit Apik, Kenagarian Sungai Talang, Guguak District, Limapuluh Regency City, the two layer chicken coops are under the auspices of PT Agung Abadi Putra Mandiri (AAPM). The purpose of this research is to find out costs, revenues, profits, and to find out the comparison of profits in closed house and open house at PT Agung Abadi Putra Mandiri. The research method used is a case study method with a quantitative approach. The data used is primary data obtained from interviews, and secondary data obtained from government agencies and company agencies as well as literature relevant to this research. The results of research during one period showed that mortality in Close House cages was 0.07 while Open House was 0.08. The calculation of the economic aspects of the Close House cage. Total production costs Rp. 17,934,489,876, receipts Rp. 24,734,338,525, and income Rp. 6,799,848,649. and for Open House cages Total production costs Rp. 16,357,916,976. Revenue IDR 21,817,412,685 and income IDR. 5,459,495,709. Close House cages have higher profits than Open House cages. With a population of 38,000 individuals, there is a difference of Rp. 663,590,752 in the closed house cage, the profit is Rp. 6,123,086,461, while in the open house cage it is Rp. 5,459,495,709 The results show that layer chickens kept in Closed House cages show very good production performance while those in Open House cages show good production performance